A Study On The Status Of Quality Empowerment Among SHG Women-A Comparison Of Tamil Nadu And Kerala - Sneha Gopeekrishna and K.T. Geetha (Journal of Commerce, Economics & Management, 2018)
Women in the lower income group category are always at a disadvantage in terms of the attainment of financial independence, financial security and social security. In such families, they are deprived of the knowledge and ability to lead their family and the situation is geared up due to male dominance and unwritten underlying norms that they should be always obliging with perseverance. They are always kept happily at ignorance. However, with the implementation of financial inclusion in the country, such deprived women have been identified and brought to a common floor called the Self Help Groups (SHGs) through Microfinance programmes, which seek the attainment of women empowerment. Though much of skill development and training programmes are catered to these women, and efforts made to get them employed through income generating ventures, back at home, they are still treated in the same manner. This is where Quality empowerment shows its vitality. Quality Empowerment is capable to make the initial transition in the attitude of an individual.SHG programmes are known to provide such quality refinement programmes .It is in such an interest, the investigator attempted to undertake a study on the status of quality empowerment whereby which 600 SHG women of Mahalir Thittam of Tamil Nadu and that of Kudumbashree of Kerala are compared.